2013
DOI: 10.1007/s12079-013-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

CCN2: a master regulator of the genesis of bone and cartilage

Abstract: CCN family member 2 (CCN2), also known as connective tissue growth factor (CTGF), has been suggested to be an endochondral ossification genetic factor that has been termed “ecogenin”, because in vitro studies revealed that CCN2 promotes the proliferation and differentiation of growth-plate chondrocytes, osteoblasts, and vascular endothelial cells, all of which play important roles in endochondral ossification. In addition to its action toward these three types of cells, CCN2 was recently found to promote the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 66 publications
0
117
0
Order By: Relevance
“…PTH and PTHrP stimulate chondrocyte differentiation and chondrogenesis of mesenchymal stem cells (Takigawa et al 1980;Kim et al 2008).However, in the late stage of the differentiation of growth-plate chondrocytes, PTHrP inhibits their terminal differentiation (Lee et al 1996).In this study, we found that CCN2 did not bind to PTHrP ( Table 1). Considering that CCN2 accelerates not only the maturation but also the hypertrophy of growth-plate chondrocytes (Takigawa 2013),at least physical interaction between CCN2 and PTHrP would not seem to be involved in the multi-functionality of CCN2. However, in light of the case of IGFs, further investigation including studies on regulation of gene expression is needed to discuss the functional relevance of interaction between them.…”
Section: Discussionmentioning
confidence: 99%
“…PTH and PTHrP stimulate chondrocyte differentiation and chondrogenesis of mesenchymal stem cells (Takigawa et al 1980;Kim et al 2008).However, in the late stage of the differentiation of growth-plate chondrocytes, PTHrP inhibits their terminal differentiation (Lee et al 1996).In this study, we found that CCN2 did not bind to PTHrP ( Table 1). Considering that CCN2 accelerates not only the maturation but also the hypertrophy of growth-plate chondrocytes (Takigawa 2013),at least physical interaction between CCN2 and PTHrP would not seem to be involved in the multi-functionality of CCN2. However, in light of the case of IGFs, further investigation including studies on regulation of gene expression is needed to discuss the functional relevance of interaction between them.…”
Section: Discussionmentioning
confidence: 99%
“…CCN2 or connective tissue growth factor has been shown to promote proliferation and differentiation of chondrocytic vessels and osteoblasts and the fusion of pre-osteoclasts (122 …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This insertion was predicted to cause a frameshift in the coding sequence of the WISP1 protein. The construct was transfected into murine embryonic stem (ES) 2 cells, and 400 G418-resistant clones were expanded and analyzed. Two ES clones, 3H4 and 4C5, were specifically targeted by the construct, determined by digestion of their DNA with ApaI, followed by Southern analysis using a 5Ј-external probe.…”
Section: Generation Of Wisp1mentioning
confidence: 99%
“…All six CCN members are found in the skeleton but with unique locations. For example, during normal skeletal development, CCN2 and CCN3 are highly expressed in cartilage (2), whereas CCN4 is largely confined to newly forming bone (3,4). Considering that many of the CCN family members bind and regulate TGF-␤, it is not surprising that they are being considered as potential therapeutic targets for diseases such as fibrosis, cancer, and osteoarthritis, in which TGF-␤ plays a crucial role in tissue pathology (1).…”
mentioning
confidence: 99%